The Influence of Credit Growth, Investment Decisions, Audit Quality, Financial Expertise of Directors and Commissioners on Sustainable Finance - Dini Justika Istiqawaty Halik; Christina Dwi Astuti (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the effect of credit growth, investment decisions, audit quality, and the financial expertise of directors and commissioners on sustainable finance in the Indonesian banking sector. The sample consisted of 47 banks listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023, with a total sample size of 136. The data used is secondary data obtained from financial reports, annual reports, and sustainability reports of banking companies. Data analysis was carried out using the multiple regression method with SPSS version 21. The results of the study show that credit growth has a significant positive effect on sustainable finance, indicating that increasing credit can support the achievement of sustainability goals in the banking sector. On the other hand, investment decisions, audit quality, and the financial expertise of directors and commissioners do not show a significant effect on sustainable finance. This finding suggests that, while other factors are important in corporate management, credit growth remains the primary factor contributing to sustainable finance in the Indonesian banking sector.